Effectiveness of a web- and mobile phone-based intervention to promote physical activity and healthy eating in middle-Aged males: Randomized controlled trial of the manup study - Duncan, Mitch J.; Vandelanotte, Corneel; Kolt, Gregory S.; Rosenkranz, Richard R.; Caperchione, Cristina M.; George, Emma S.; Ding, Hang; Hooker, Cindy; Karunanithi, Mohan; Maeder, Anthony J.; Noakes, Manny; Tague, Rhys; et al. (My University, 2014)
Background: The high number of adult males engaging in low levels of physical activity and poor dietary practices, and the health risks posed by these behaviours, necessitate broad-reaching intervention strategies. IT-based (web and mobile phone) interventions can be accessed by large numbers of people, yet there are few reported IT-based interventions targeting males’ physical activity and dietary practices. Objective: This study examines the effectiveness of a 9-month IT-based intervention to improve the physical activity, dietary behaviours and health literacy in middle-aged males compared to a print-based intervention. Methods: Participants, recruited offline (e.g. newspaper ads), were randomized into either an IT-based or print-based intervention arm on a 2:1 basis in favour of the fully automated IT-based arm. Participants were adult males aged 35-54 years living in two regional cities in Queensland Australia who could access the internet, owned a mobile phone and were able to increase their activity level. The intervention, ManUp, was informed by social cognitive and self regulation theories and was specifically designed to target males. Educational materials were provided and self-monitoring of physical activity and nutrition behaviours was promoted. Intervention content was the same in both intervention arms, only the delivery mode differed, and content could be accessed throughout the 9-month study period. Participants’ physical activity, dietary behaviours, and health literacy were measured using online surveys at baseline, 3 months and 9 months. Results: A total of 301 participants completed baseline assessments, 205 in the ITbased arm and 96 in the print-based arm. A total of 124 participants completed all three assessments. There were no significant between group differences in physical 5 activity and dietary behaviours (p ≥0.05). Participants reported an increased number of minutes and sessions of physical activity at 3 months (b(exp)=1.45, 95% CI=1.09-1.95; b(exp)=1.61, 95% CI=1.17-2.22) and 9 months (b(exp)=1.55, 95% CI=1.14-2.10; b(exp)=1.51, 95% CI=1.15-2.00). Overall dietary behaviours improved at 3 months (b(exp)=1.07, 95% CI=1.03-1.11) and 9 months (b(exp)=1.10, 95% CI=1.05-1.13). The proportion of participants in both groups eating higher-fibre bread and low-fat milk increased at 3 months (b(exp) = 2.25, 95% CI = 1.29-3.92; b(exp)=1.65, 95% CI = 1.07-2.55). Participants in the IT-based arm were less likely to report that 30 minutes of physical activity per day improves health (b(exp)=0.48, 95% CI=0.26-0.90) and more likely to report that vigorous intensity physical activity 3 times per week is essential (b(exp)=1.70, 95% CI=1.02-2.82). The average number of logins to the IT-platform at 3 and 9 months was 6.99 (SE=0.86) and 9.22 (SE=1.47), respectively. The average number of self-monitoring entries at 3 and 9 months was 16.69 (SE=2.38) and 22.51 (SE=3.79), respectively. Conclusions: The ManUp intervention was effective in improving physical activity and dietary behaviours in middle aged males with no significant differences between IT- and print-based delivery modes.
Keywords: Physical activity; Dietary behaviours; Mobile phone; Web-based; RCT